Emergent geomorphic–vegetation interactions on a subalpine alluvial fan. Issue 1 (14th October 2015) - Lane, Stuart N.; Borgeaud, Laure; Vittoz, Pascal
Abstract: Following perturbation, an ecosystem (flora, fauna, soil) should evolve as a function of time at a rate conditioned by external variables (relief, climate, geology). More recently, biogeomorphologists have focused upon the notion of co‐development of geomorphic processes with ecosystems over very short through to very long (evolutionary) timescales. Alpine environments have been a particular focus of this co‐development. However, work in this field has tended to adopt a simplified view of the relationship between perturbation and succession, including: how the landform and ecosystem itself conditions the impact of a perturbation to create a complex spatial response impact; and how perturbations are not simply ecosystem destroyers but can be a significant source of ecosystem resources. What this means is that at the within landform scale, there may well be a complex and dynamic topographic and sedimentological template that co‐develops with soil, flora and fauna. Here, we present and test a conceptual model of this template for a subalpine alluvial fan. We combine detailed floristic inventory with soil inventory, determination of edaphic variables and analysis of historical aerial imagery. Spatial variation in the probability of perturbation of sites on the fan surface was associated with down fan variability in the across‐fan distribution of fan ages, fan surface channel characteristics and fan surface sedimentology. Floristic survey confirmed that these edaphic factors distinguished site floristic richness and plant communities up until the point that the soil–vegetation system was sufficiently developed to sustain plant communities regardless of edaphic conditions. Thus, the primary explanatory variable was the estimated age of each site, which could be tied back into perturbation history and its spatial expression due to the geometry of the fan: distinct plant communities were emergent both across fan and down fan, a distribution maintained by the way in which the fan dissipates potentially perturbing events. Copyright © 2015 John Wiley & Sons, Ltd.